Representation of the Hierarchy of Needs of Laila's Character through Speech Acts in the Novel Majnun Layla by Nizami Ganjavi - Alawy , Ahmad; Hidayatullah, Moch Syarif (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
Literary works not only represent linguistic aesthetics but also portray the psychological conditions of characters through dialogues and social relations within the story. This study aims to describe illocutionary and perlocutionary speech acts as well as the psychological condition of Laila in the novel Majnun Layla by Nizami Ganjavi based on Abraham Maslow’s hierarchy of needs theory. This research employed a descriptive qualitative method using pragmatics and literary psychology approaches. The data consisted of dialogues and utterances found in the fourth chapter of the novel collected through observing and note-taking techniques. The data were analyzed using the pragmatic equivalent method and Miles and Huberman’s analysis model through the stages of data reduction, data display, and conclusion drawing. The findings revealed that the illocutionary speech acts identified in the novel include assertive, expressive, and directive acts, while perlocutionary acts appeared through emotional responses such as anger, threats, sadness, and psychological pressure among the characters. Based on Maslow’s hierarchy of needs theory, Laila’s psychological condition is dominated by safety needs, belonging and love needs, and self-esteem needs. These needs are not fully fulfilled due to social pressure, separation from Qays, and family domination over Laila’s life. This study demonstrates that speech acts in literary dialogues function not only as communication tools but also as representations of psychological conflicts and social relations within literary works.